Measurement of Several Hematological and Serological Parameters in Patients with Scabies - Y. Al-Fadhly, Mariam; A. Al-Marsomy , Wasan; ., Hiba H. Maqdasi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
People often refer to scabies as the "7-year itch," but it is more appropriate to refer to it as a "family disease" (1, 15). Scabies mites penetrate the stratum corneum epidermis of the skin at the onset of infection (2, 16). The current study involved the collection of blood samples from a patient group infected with scabies disease, comprising sixty individuals, and a control group of sixty individuals who were in good health. The tests showed that there were no statistically significant differences between the scabies patients and the control group for Hb (12.86± 0.31, 12.88± 0.20), PCV (34.40±0.94, 40.35±0.59), and platelets (244.80±9.58, 237.23±8.97), Respectively. There were also significant differences at the 0.001 level between the two groups of patients and the control group for white blood cells (WBC), lymphocytes, neutrophils, eosinophils, monocytes, and basophils. These were (11.09±0.20, 7.50 ±0.16), (5.05±0.16, 2.27 ±0.06), (8.23±0.10, 3.75±0.11), (0.828±0.7, 0.415±0.03), (0.498±0.02, 0.459±0.03), and (0.329±0.02, 0.102 ± 0.01), respectively. However, the measurement of immunoglobulins (IgA and IgE) revealed non-significant differences in the value of IgA for scabies patients (130.73 ± 10.38) compared to the control group (115.55 ± 4.60). However, the IgE ratio resulted in high significant differences at level (P≤0.01) between patients (36.59 ±5.06) and control (13.56 ±0.89).